The roles of foreign direct investment inflow in carbon emission: A Malaysian perspective - Tan, Zhi Lin; Lian, Wye Loon; Chau, Keen Zhi (2023)
In recent years, globalization has led to the acceleration of capital in the world, especially foreign direct investment (FDI), which promotes the economic growth of the host country. As the promotion of the economy, which also leads to carbon emissions. We study in a developing country like Malaysia, are boosting economic growth. However, this economic progress has a downside, it often leads to more pollution and carbon emissions. In these recent years there hasn’t been much research on this connection in the context of Malaysia. In this study, we aim to examine the effects of FDI on Malaysia’s carbon emissions from 1990 to 2020. We employ the ARDL model and incorporate relevant control variables to unravel the complex relationship between economic growth and carbon emissions in Malaysia. Our research result indicates that in the long run, FDI, population, and trade has a positive relationship to the carbon emission. The GDP per capita has a negative relationship in the long run. Significantly, the study's outcomes offer essential policy suggestions directed towards policymakers.